2016
DOI: 10.3934/mbe.2016.13.101
|View full text |Cite
|
Sign up to set email alerts
|

The global stability of coexisting equilibria for three models of mutualism

Abstract: We analyze the dynamics of three models of mutualism, establishing the global stability of coexisting equilibria by means of Lyapunov's second method. This further establishes the usefulness of certain Lyapunov functionals of an abstract nature introduced in an earlier paper. As a consequence, it is seen that the use of higher order self-limiting terms cures the shortcomings of Lotka-Volterra mutualisms, preventing unbounded growth and promoting global stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…We can also have a combination of the situations shown in the models (9) and (13), in which x 2 reduces the death rate of x 1 and x 1 increases the birth rate of x 2 , which allows for the modelling of interacting species with very different vital parameters, as follows:…”
Section: Models With Asymmetric Mutualism Effectsmentioning
confidence: 99%
See 3 more Smart Citations
“…We can also have a combination of the situations shown in the models (9) and (13), in which x 2 reduces the death rate of x 1 and x 1 increases the birth rate of x 2 , which allows for the modelling of interacting species with very different vital parameters, as follows:…”
Section: Models With Asymmetric Mutualism Effectsmentioning
confidence: 99%
“…Here, the assumptions on a 1 and f 1 are those used in the analysis of model (9) while for f 2 and a 2 we consider the assumptions from Equation (13). Again, the bounding theorems presented above hold with very similar proofs and the Dulac function is ϕ(…”
Section: Models With Asymmetric Mutualism Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Georgescu et al (2016) have analyzed the dynamics of three models of mutualism and establishing the global stability via the method of Lyapunov functional. The authors found that the use of higher-order self-limiting terms cures the shortcomings of Lotka-Volterra mutualisms, preventing unbounded growth and promoting global stability.…”
Section: Introductionmentioning
confidence: 99%